Nursing older people at a glance - Tetley, Josie; Cox, Nigel; Jack, Kirsten; Witham, Gary; Peate, Ian (Wiley Blackwell, 2018)
"As the environment of care continues to evolve to promote person-centredness, dignity, health, and wellbeing, for nurses working with older people, this can be challenging. Nursing Older People at a Glance is a timely publication which provides an overview of key concepts that nurses need to know in order to care for older people in a wide range of settings. Divided into six sections, it explores a range of themes such as person-centred care, health and wellbeing, health promotion, and the complexity of older people's care, encompassing mental wellbeing, diverse communities and learning disability. With a strong focus on dignity in care throughout, Nursing Older People at a Glance will readily equip undergraduate and post-qualification nurses with the knowledge and skills required to care for older people in a competent and compassionate manner"- Resumé vydavatel
Keywords: ošetřovatelství; geriatrie; péče o seniory; lékařská péče; ošetřovatelská péče; nursing; geriatrics; older people’s care; medical care; nursing care; sborníky; papers of several authors